Exploring the Influence of Self-Efficacy, Tolerance for Risk, and Freedom in Work on Entrepreneurship Interests among University Students: A Study at Klabat University - Clara Angelia; Saulina Devi; Rivera Sirmon (Indonesia Accounting Research Journal, 2024)
This research investigates the influence of self-efficacy, tolerance for risk, and freedom in work on entrepreneurship interests among Klabat University students. Drawing upon theoretical frameworks in entrepreneurship and psychology, the study aims to elucidate the psychological factors shaping students' aspirations towards entrepreneurship. A quantitative research design is employed, utilizing survey questionnaires to collect data from a representative sample of students. Statistical analysis techniques, including correlation analysis, regression analysis, and structural equation modeling, are utilized to examine the relationships between self-efficacy, tolerance for risk, freedom in work, and entrepreneurship interests. The findings reveal significant positive relationships between self-efficacy and entrepreneurship interests, as well as between freedom in work and entrepreneurship interests. However, tolerance for risk does not emerge as a significant predictor of entrepreneurship interests. These findings underscore the importance of fostering self-belief and empowerment among students to cultivate entrepreneurial mindsets and skills. The implications of the findings for theory, practice, and future research are discussed, emphasizing the need for targeted interventions and support mechanisms to nurture entrepreneurial aspirations among university students. Overall, this research contributes to our understanding of the psychological determinants of entrepreneurship interests and provides insights for promoting entrepreneurship education and policy initiatives.